1989
DOI: 10.1126/science.2526370
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Angiotensin-Converting Enzyme Prevent Myointimal Proliferation After Vascular Injury

Abstract: The role of a local angiotensin system in the vascular response to arterial injury was investigated by administering the angiotensin-converting enzyme (CE) inhibitor cilazapril to normotensive rats in which the left carotid artery was subjected to endothelial denudation and injury by balloon catheterization. In control animals, by 14 days after balloon injury, the processes of smooth muscle cell (SMC) proliferation, migration of SMCs from the media to the intima, and synthesis of extracellular matrix produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
364
0
8

Year Published

1991
1991
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,038 publications
(386 citation statements)
references
References 23 publications
14
364
0
8
Order By: Relevance
“…The potential of angiotensin-converting enzyme (ACE) inhibitors in prevention of neointima formation was ®rst addressed in a rat model of carotid artery balloon injury (Powell et al, 1989). This protective e ect was mainly attributed to inhibition of the ACE-induced generation of angiotensin II a potent vasopressor implicated in vascular smooth muscle cell (SMC) growth (Itoh et al, 1993), proliferation (Huckle & Earp, 1994), and migration (Farhy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of angiotensin-converting enzyme (ACE) inhibitors in prevention of neointima formation was ®rst addressed in a rat model of carotid artery balloon injury (Powell et al, 1989). This protective e ect was mainly attributed to inhibition of the ACE-induced generation of angiotensin II a potent vasopressor implicated in vascular smooth muscle cell (SMC) growth (Itoh et al, 1993), proliferation (Huckle & Earp, 1994), and migration (Farhy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that: (1) vascular hypertrophy is reduced by angiotensinconverting enzyme (ACE) inhibitors or Ang II receptor antagonists; [1][2][3][4] (2) components of the reninangiotensin system, such as ACE, 5,6 and angiotensinogen mRNA 7 are activated or increased in the area of vascular hypertrophy; and (3) Ang II promotes migration, proliferation, and hypertrophy of vascular smooth muscle cells, and generation of extracellular matrix, as seen in in vitro and in vivo models. [8][9][10][11] Because intima hyperplasia after balloon injury could be reduced by treatment of ACE inhibitors in rats, 3 ACE inhibitors were expected to be effective in clinical use. However, ACE inhibitors failed to reduce the restenosis seen after clinical PTCA.…”
Section: Introductionmentioning
confidence: 99%
“…The growth-promoting effects of Ang II are modulated, under normal conditions, by endothelium-derived factors. Removal of the endothelium, for example by balloon injury, may alter the vascular structure and promote the development of intimal hyperplasia, and this may be reverted by ACE inhibition in experimental animal models [17,18].…”
Section: Pathobiology Of Angiotensin IImentioning
confidence: 99%
“…Increased tissue angiotensin concentrations are probably critical for the neointima development, as shown by the fact that, in several animal species, ACE-inhibitors and AT 1 receptor antagonists can prevent neointimal hyperplasia in response to vascular injury [18,20]. The removal of endothelium, for example after balloon injury, allows angiotensin to exert a direct growth-promoting effect on vascular smooth muscle cells [4].…”
Section: Ang II In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation